1996
DOI: 10.1016/0013-4694(96)95601-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of EEG power spectra in early life

Abstract: We measured the electroencephalogram (EEG) in 209 5 year old monozygotic (MZ) and dizygotic (DZ) twin pairs to estimate the relative contribution of genetic and environmental factors to EEG power spectra in early life. Data from same-sex and from oppositesex twin pairs were used to test for sex differences in genetic influences. Results showed high concordance for EEGs of MZ twins for absolute and relative power in 6, 0, al, a2, t51 and/~2 bands. A model with additive genetic and unique environmental influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 33 publications
7
57
1
Order By: Relevance
“…In this same sample of twins, we have shown that individual differences in background EEG (van Baal, De Geus, & Boomsma, 1996) and in event-related brain potentials (ERP-P3) are highly heritable both at ages 5 and 7 (van Baal et al, this issue). Although it is difficult to relate neural and behavioral functioning (Benno, 1990), these results might suggest that high heritabilities of indexes of nervous system functioning precede the high heritabilities that are observed for IQ later in life.…”
Section: Discussionmentioning
confidence: 95%
“…In this same sample of twins, we have shown that individual differences in background EEG (van Baal, De Geus, & Boomsma, 1996) and in event-related brain potentials (ERP-P3) are highly heritable both at ages 5 and 7 (van Baal et al, this issue). Although it is difficult to relate neural and behavioral functioning (Benno, 1990), these results might suggest that high heritabilities of indexes of nervous system functioning precede the high heritabilities that are observed for IQ later in life.…”
Section: Discussionmentioning
confidence: 95%
“…The register contains around 50% of all Dutch twins born after 1986 (Boomsma et al, 1992). All 209 pairs participated in a study of the development of brain-activity and cognitive development at ages 5 and 7 (Van Baal et al, 1996;Boomsma & Van Baal, 1998). Families were selected on the basis of the age and zygosity of the twins, and of their city of residence.…”
Section: Participantsmentioning
confidence: 99%
“…In an ongoing longitudinal study of brain function (Van Baal, 1997) and cognition in young Dutch twins data on six intelligence subtests were collected in 5-year-old boys and girls. This paper explores the genetic and environmental structure of specific cognitive abilities by evaluating a number of alternative factor models to the six measures of verbal and nonverbal IQ.…”
Section: Introductionmentioning
confidence: 99%
“…For example, large-scale studies that compared similarities of EEG characteristics between genetically identical, monozygotic (MZ) twins and nonidentical dizygotic (DZ) twins estimated high heritabilities for power in the classical EEG frequency bands. For power in delta, theta, alpha, and beta bands heritabilities range from 55% to 90% in children [Van Baal et al, 1996] and 70% to 90% in adolescents [Smit et al, 2006;van Beijsterveldt et al, 1996;Zietsch et al, 2007] and adults [Smit et al, 2005]. These findings suggest that, besides brain anatomy [Toga and Thompson, 2005], resting-state brain function is also under strong genetic control.…”
Section: Introductionmentioning
confidence: 99%